An Analysis of Idioms in Humorous Dialogues of Legally Blonde Movie (2001): A Semantic Study - Muhammad Rizky Putra Pangestu; Vinaswa Mujianto Putri; Lisa Suhayati (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This research examines idiomatic expressions found in the humorous dialogues of Legally Blonde (2001) using Leech’s semantic theory. The study aims to identify the idioms used in the film, describe their meanings based on semantic interpretation, and explain how they contribute to humor. A descriptive qualitative method was applied, with the film script serving as the primary data source. The researcher carefully read the script, selected scenes containing humorous or informal conversations, and identified idioms spoken by the characters. Each idiom was then analyzed in context and categorized into four types: figurative, slang/colloquial, euphemistic, and hyperbolic. The findings reveal 17 idioms that support the film’s comedic tone. Slang and colloquial idioms appear most frequently, reflecting the informal and youthful atmosphere of the film. Figurative idioms express emotion and personality, euphemistic soften direct statements, and hyperbolic idioms create exaggerated effects that strengthen humor. Overall, the study shows that idioms not only function as linguistic expressions but also play an important role in developing character identity and enhancing the humorous style of the film